Language Disorders and ADD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The prevalence rates of speech and language disorders and ADD in 116 children referred for psychiatric services were determined at the Ontario Association of Children's Mental Health Centres and the Dept of Psychiatry, Hospital for Sick Children, Toronto, Canada.